Programa pré-escolar para crianças de risco para os transtornos de linguagem: quem responde à intervenção? - Silveira, Heloisa Goncalves Da [UNIFESP] (2020)
Objectives: 1) to explore whether the individuals who best respond to the intervention have a common language profile and, if so, describe this profile; 2) to analyze if children with a language profile suggestive of LD will respond better to the intervention, being more susceptible to stimulation. In contrast, children with a language profile suggestive of SLI will underperform, not responding or responding poorly to the intervention. Method: This is an exploratory retrospective study that aims to investigate and identify the language profile of children who responded to the early oral language intervention program adapted to the Brazilian reality. The participating preschools were from Rio Claro. Students were selected based on teachers' evaluation of children's behavior and performance in language tasks. This trial was based on a questionnaire to identify children with communication difficulties, developed especially for the research. The final sample consisted of the 16 children from each school that presented the lowest language indices (n total = 128; considering the eight participating schools). Half of the children in each school were randomly assigned to language intervention, and half to the control group, using stratified randomization to control the effects of early language skills. Results: The results emphasized differences between the intervention and control group in the gains related to the taught vocabulary (Voc. Ensinado) and the phonological awareness (CF) with an average. No differences were found between the groups in any standardized untrained language measure. Based on the skills trained, clusters were generated with individuals who participated in the intervention. The group Gain CF obtained greater gain in phonological awareness. The Taught Vocabulary Gain Group due to its greater improvement in vocabulary taught during the intervention. The third group, Worst Gain, was the group with the lowest gain in both abilities when compared to the others. Children who made up the groups with the highest gains had poor initial performance in these skills, thus obtaining greater gain margin for each group after the intervention. Conclusion: The study showed that the variables with the greatest influence on the environment tend to respond more clearly to the proposed intervention process.